PENYULUHAN POTENSI KEGIATAN WIRAUSAHA DESA RAMAH LINGKUNGAN DI KABUPATEN MANOKWARI - Rahayu, Yuyun Puji; Tewernusa, Ketysia Imelda; Semet, Maria Magdalena (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
Abstract Dissemination of information to villages, especially in remote, outermost and smallest areas about strategic issues of welfare improvement that can be developed has not been widely implemented. By taking the example of a village located on the outskirts of the city, the purpose of outreach activities about the potential for entrepreneurial activities in the village is to disseminate knowledge and information as well as provide motivation to the population, most of whom only work as subsistence farmers. The result of this activity is an increase in the knowledge of the extension participants in terms of carrying out activities that have economic value using natural resources that are already available in the village. Thus, residents can create additional income opportunities without leaving their main activities as farmers. Keywords: community empowerment, village entrepreneurship, environmental economy Abstrak Penyebarluasan informasi kepada desa, terutama di daerah terpencil, terluar dan terkecil tentang isu-isu straegis peningkatan kesejahteraan yang dapat dikembangkan belum banyak dilaksanakan. Dengan mengambil contoh kampung yang terletak dipinggiran kota, tujuan kegiatan penyuluhan tentang potensi kegiatan wirausaha di desa adalah penyebarluasan pengetahuan dan informasi serta memberikan motivasi kepada penduduk yang sebagian besar hanya bekerja sebagai petani subsisten. Hasil kegiatan ini adalah meningkatnya pengetahuan peserta penyuluhan dalam hal melakukan kegiatan yang bernilai ekonomis dengan menggunakan sumber daya alam yang sudah tersedia di desa. Dengan demikian penduduk dapat menciptakan peluang tambahan pendapatan tanpa meinggalkan kegiatan utamanya sebagai petani. Keywords: pemberdayaan masyarakat, wirausaha desa, ekonomi lingkungan